Diet breadth of Gynaephora groenlandica (Lepidoptera: Erebidae): is polyphagy greater in alpine versus Arctic populations?. Issue 2 (29th May 2014) - Barrio, I.C.; Hik, D.S.; Liu, J.Y.
Abstract: Gynaephora groenlandica (Wocke) (Lepidoptera: Erebidae) is a cold-adapted species, whose life history traits are dictated by cold and short Arctic summers. We used a recently discovered alpine tundra population in southwestern Yukon, Canada to investigate local adaptations to habitats with different environmental conditions (alpine versus Arctic). Using cafeteria-type experiments and field observations we examined the diet breadth of alpine populations of G. groenlandica beringiana Schmidt and Cannings, and compared these to published data on High Arctic populations of G. groenlandica groenlandica and to the closely related G. rossii Curtis. Gynaephora groenlandica beringiana appears to have a broader diet than High Arctic populations, but similar to that exhibited by alpine populations of G. rossii . Such trends could emerge from reduced synchrony between herbivores and their host plants in less extreme environments, and possibly from a reduced incidence of parasitoids in the life cycle of these populations. Our findings indicate the larval host plant plasticity of G. groenlandica in different environments, and are relevant to predictions regarding the fate of these populations under climate warming scenarios. Résumé: Gynaephora groenlandica (Wocke) (Lepidoptera: Erebidae) est une espèce adaptée au froid, dont les traits d'histoire de vie sont dictés par des étés Arctiques froids et courts. Nous avons utilisé une population de toundra alpine récemment découverte dans le sud-ouest du Yukon (Canada) pour étudier les adaptations locales à des environnements différents (alpins vs. arctiques). Utilisant des expériences de type « cafeteria » et des observations de terrain, nous avons examiné l'amplitude alimentaire de populations alpines de G . groenlandica beringiana Schmidt and Cannings, et nous les avons comparées aux données publiées sur des populations de G . groenlandica du Haut Arctique et des populations de G . rossii Curtis, espèce qui lui est étroitement apparentée. Gynaephora groenlandica beringiana semble avoir une amplitude alimentaire plus large que celle de populations du Haut Arctique, mais similaire à celle de populations alpines de G . rossii . De telles tendances pourraient résulter d'une synchronisation réduite entre herbivores et leurs plantes hôtes dans des environnements alpins, moins extrêmes, et éventuellement d'une incidence plus réduite des parasitoïdes dans le cycle de vie de ces populations. Nos résultats indiquent la plasticité du choix de la plante hôte par la chenille de G . groenlandica dans des environnements différents. Ces résultats ont une importance pour des prédictions quant à l'avenir de ces populations sous des scénarios de réchauffement climatique.